Optimization of Scaffolding Method in Aqidah Akhlak Learning to Improve Clean and Healthy Living Behavior of Students at MIS Nurul Huda - Ulfah, Yanti Nur; Sulaeman, Wono; Suryani, Yani; Faqori, Yudha Bima; Mawati, Yelmi (Jurnal Cendekia Islam Indonesia, 2025)
Awareness of the importance of healthy and clean living is a fundamental aspect in basic education, especially in learning Akidah Akhlak. However, there are still many students who do not understand and apply healthy living habits due to less interactive learning methods. This study aims to analyze the effectiveness of the scaffolding method in increasing awareness of healthy and clean living in grade 1 students of MI Nurul Huda. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was carried out thematically with the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the scaffolding method was effective in increasing student understanding and participation. The application of techniques such as gradual guidance, group discussions, and direct practice helped students better understand the concept of cleanliness and health. In addition, the results of academic tests showed a significant increase in student understanding after this method was applied. The challenges faced include differences in student understanding levels, so that more varied learning strategies are needed. In conclusion, the scaffolding method can be an effective approach in instilling healthy and clean living values in students from an early age.